2018
DOI: 10.1088/1361-6560/aaaffe
|View full text |Cite
|
Sign up to set email alerts
|

Anin silicoframework to analyze the anisotropic shear wave mechanics in cardiac shear wave elastography

Abstract: Shear wave elastography (SWE) is a potential tool to non-invasively assess cardiac muscle stiffness. This study focused on the effect of the orthotropic material properties and mechanical loading on the performance of cardiac SWE, as it is known that these factors contribute to complex 3D anisotropic shear wave propagation. To investigate the specific impact of these complexities, we constructed a finite element model with an orthotropic material law subjected to different uniaxial stretches to simulate SWE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Since shear waves in the myocardium could be affected by several factors such as shape, anisotropy, and inhomogeneity [27,28] the precise quantitative relation between the naturally-occurring shear waves' velocity and the intrinsic stiffness is difficult to establish directly. We therefore quantify only the propagation velocity of the shear waves, assuming a monotonic relation with the tissue stiffness [1,29].…”
Section: Introductionmentioning
confidence: 99%
“…Since shear waves in the myocardium could be affected by several factors such as shape, anisotropy, and inhomogeneity [27,28] the precise quantitative relation between the naturally-occurring shear waves' velocity and the intrinsic stiffness is difficult to establish directly. We therefore quantify only the propagation velocity of the shear waves, assuming a monotonic relation with the tissue stiffness [1,29].…”
Section: Introductionmentioning
confidence: 99%
“…Villemain et al (Villemain et al, 2018) reported a FA of 0.238±0.068 for the mid cardiac wall in healthy volunteers, and a decreased FA of 0.133±0.073 in patients with hypertrophic cardiomyopathy (HCM). (Caenen et al, 2018). The black dotted line in the slices represents the actual myocardial fiber orientation in the model.…”
Section: Anisotropymentioning
confidence: 99%
“…In the context of this work (shear wave propagation in soft tissues) we choose L = 10 −2 m and T = 10 −2 s, since our main focus is the propagation of shear waves (1 m s −1 to 10 m s −1 ) in a rectangular slab of an organ (e.g. in some volume of 6 cm × 6 cm × 2 cm of the left ventricle of the heart [29]). To model the myocardial tissue, in accordance with [19,28,29,30,26] we choose…”
Section: Definition Of a Parametric Family Of Problemsmentioning
confidence: 99%
“…in some volume of 6 cm × 6 cm × 2 cm of the left ventricle of the heart [29]). To model the myocardial tissue, in accordance with [19,28,29,30,26] we choose…”
Section: Definition Of a Parametric Family Of Problemsmentioning
confidence: 99%